Testing the CAPM and the APT: Evidence from the UK Stock Market - WANG, Zheng (2010)
Asset pricing is a very important issue in the financial field. A variety of models can be applied for such issue. This paper focuses on both the Capital Asset Pricing Model (CAPM) and the Arbitrage Pricing Theory (APT). The two-pass regression is used for the empirical tests. In the CAPM test, the FTSE ALL-share index is used as proxy for the market portfolio. In the APT test, the macroeconomic variables approach is applied due to the possible impact of the recent financial crash on the UK stock market. Inflation, industrial production, 10-year UK government securities, and US Dollar into Sterling rate are selected as the potentially influential factors. The APT is in essence a class of models since the factors under the APT framework can be selected according to researchers’ subjective views. In this study we select a very specific member (i.e. the four macroeconomic factors) of this class and also the CAPM is an essentially member of the class with single specific factor. Therefore, this study aims to examine which of the two APT members can better explain for the UK stock market during the financial turmoil period from 2005 to 2009. Consequently, while the market Beta under the CAPM framework proves to be insignificant in explaining the asset returns, two factors of the APT (i.e. industrial production and US Dollar into Sterling rate) turn out to be fairly significant. The APT allows us to link the current financial condition to the model test, whereas the CAPM’s single factor (i.e. market Beta) fails to offer such flexibility. This is in fact a significant advantage of the APT over the CAPM.